First Comparison Report of the SAPIEN S3 Ultra Balloon Expandable Transcatheter Heart Valve. Issue 6 (1st November 2020) - Luke, David; Kehl, Devin; Flagg, Eric; Sheridan, Brett; Spies, Christian; Walsh, Joseph; Ferreira, Milena; Sudat, Sylvia Ek; Daniels, David
ABSTRACT: Background: Even mild paravalvular leak (PVL) is associated with worse quality of life and increased mortality. The Ultra transcatheter heart valve (THV) is intentionally designed to reduce PVL. However, there are limited data comparing the degree of PVL between S3 and Ultra THVs. We compared the degree of PVL between the SAPIEN S3 Ultra (Ultra) and SAPIEN S3 (S3) THV. Methods: Transcatheter aortic valve replacement (TAVR) patients who received an S3 or Ultra THV from September 1, 2017 to August 15, 2019 were identified. The THV oversizing percentage, the LVOT calcification and annular calcific nodularity were measured on a blinded re-review of pre-TAVR CTs. The degree of PVL was assessed on a blinded re-review of post-implantation echocardiograms. The demographics, pre-TAVR anatomic characteristics, and degree of PVL were compared between the S3 and Ultra groups using standard statistical methods. Results: Thirty-two cases met the inclusion criteria for each group. There were no significant differences in baseline anatomic characteristics or in post-implant mean pressure gradient. There was a trend toward increased balloon post-dilations in the S3 group. There was no moderate or severe PVL in any case. There was significantly less mild PVL in the Ultra group compared to the S3 group (22% vs. 0%, P = 0.006). Conclusion: The new generation Edwards SAPIEN S3 Ultra valve is associated with significantly less PVL with similar post-implant hemodynamics in comparison to the previous generation THV. Abbreviations: TAVR: Transcatheter Aortic Valve Replacement; THV: Transcatheter Heart Valve; PVL: Paravalvular Leak; S3: Edwards SAPIEN S3 Transcatheter Heart Valve; Ultra: Edwards SAPIEN S3 Ultra Transcatheter Heart Valve; SHIRB: Sutter Health Institutional Review Board; CT: Computed Tomography; TTE: Transthoracic Echocardiogram; LVOT: Left Ventricular Outflow Tract; MPG: Mean Transaortic Pressure Gradient; Vmax: MaximumTransaortic Velocity; PET: Polyethylene Terephthalate